Comparison of the effects of BDNF/TRKB signalling on metabolic biomarkers in the liver of sedentary and trained rats with normal and knockout BDNF genotypes - Grzelak, Norbert; Kaczmarek, Dominik; Mrówczyński, Włodzimierz (Frontiers in Physiology, 2023)
The effect of brain-derived neurotrophic factor (BDNF) on the modulation of metabolic processes in the liver is poorly understood. Therefore, the aim of this study was to investigate whether hepatic concentrations or activities of metabolic biomarkers depend on altered BDNF/TrkB content in the liver, resulting from different BDNF genotypes of rats. In addition, it was assessed whether 5-week moderate endurance training modifies the levels of BDNF/Trk-B signaling and studied hepatic markers.Experiments were performed on wild-type and heterozygous BDNF knockout (HET, SD-Bdnf) rats, which were divided into four groups: control with normal genotype (Bdnf+/+), control with BDNF knockout genotype (Bdnf+/-), trained with normal genotype (Bdnf+/+T) and trained with BDNF knockout genotype (Bdnf +/-T). BDNF/TrkB concentrations as well as selected metabolic biomarkers including lipids -total cholesterol (CHOL), low-density lipoprotein (LDL), triglycerides (TG); enzymes -alanine aminotransferase (ALAT), aspartate aminotransferase (ASAT), gamma-glutamyl transferase (GGT), lactate dehydrogenase (LDH), alkaline phosphatase (ALP); hormones -insulin (INS) and leptin (LEPT) as well as interleukin-6 (IL-6) as regeneration indicator were measured directly in liver homogenates.The study showed that Bdnf+/-rats exhibited reduced BDNF/TrkB signaling (BDNF, p< 0.0001; Trk-B, p= 0.0005), altered lipid levels (CHOL, p<0.0001; LDL, p<0.0001; TG, p= 0.0006) and reduced hepatic ALAT (p= 0.0004) and GGT (p<0.0001) activity, which may contribute to hepatic steatosis and obesity, as well as indicate impairment of specific metabolic pathways in the liver. Interestingly, endurance training did not alter hepatic BDNF and TrkB content, but improved ALAT (p= 0.0366) and ASAT (p= 0.0191) activities and increased hepatic IL-6 (p= 0.0422) levels in Bdnf +/-rats, suggesting enhanced liver regeneration in animals with BDNF allele loss.